2019
DOI: 10.2147/hiv.s222611
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence Of Undernutrition And Associated Factors Among Adults Receiving First-Line Antiretroviral Treatment In Public Health Facilities Of Arba Minch Town, Southern Ethiopia</p>

Abstract: IntroductionAccess to antiretroviral drugs for all infected persons in need is a global health priority. The primary goals of initiating antiretroviral drugs are to suppress human immunodeficiency virus viral replication and to restore immune function. However, adequate nutrition is necessary to manage opportunistic infections and to maintain the immune system. Therefore, this study aimed to determine the recent prevalence of undernutrition and associated factors among HIV patients receiving first-line antiret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 12 publications
10
22
0
2
Order By: Relevance
“…This study found a higher prevalence of undernutrition in those who were on ART for a shorter duration (15%) than those who had been on ART for a longer duration (11%), although the association was not significant. This observation is supported by findings from other studies, in which those who had been on ART for a short duration were almost twice as undernourished as those who had been taking the ART for a longer duration [11,44]. The explanation for this observation could be that patients who are undernourished at the time of their enrolment on ART, who might have been suffering from a more advanced stage of the disease, become healthier and gain weight over time, with their recovery from opportunistic infections [41,45].…”
Section: Discussionsupporting
confidence: 81%
“…This study found a higher prevalence of undernutrition in those who were on ART for a shorter duration (15%) than those who had been on ART for a longer duration (11%), although the association was not significant. This observation is supported by findings from other studies, in which those who had been on ART for a short duration were almost twice as undernourished as those who had been taking the ART for a longer duration [11,44]. The explanation for this observation could be that patients who are undernourished at the time of their enrolment on ART, who might have been suffering from a more advanced stage of the disease, become healthier and gain weight over time, with their recovery from opportunistic infections [41,45].…”
Section: Discussionsupporting
confidence: 81%
“…Participants with CD4+ < 200 cell/μl had 1.84 times chance of being undernourished compared to those with CD4+ cells/μl count > 500 (AOR = 1.84; 95% CI: 1-3.36). Other studies done in Ethiopia [19,21,23,24] showed similar associations. This result is also in line with other studies done in developed and developing countries [10,[38][39][40].…”
Section: Discussionsupporting
confidence: 72%
“…But this is higher than other studies done in Tanzania (19%) [15] and Zimbabwe (10%) [16]. Similarly, it is also higher than other studies done in Ethiopia such as in Arba Minch Town (23.2%) [21], 12.3% in Dilla University [19], and 23.2% in Dembia district [23]. This different result among different studies could be explained by the discrepancy in health care awareness of the community and the sample size difference.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Further analysis revealed that CD4 + T cell counts below 350 or 200 cells/μl were significantly associated with malnutrition. In the case of malnutrition, changes in the levels of immune cell populations, hormones, and cytokines lead to changes in the metabolism of immune cells, thereby affecting immune function (Oumer et al, 2019). During the whole process of HIV infection, nutritional status and immune function are closely related and interact.…”
Section: Effects Of Gut Microbiota Changes On Immune Reconstitution Omentioning
confidence: 99%